2011
DOI: 10.1074/jbc.m110.190959
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Analysis of High Iron Toxicity in Yeast

Abstract: Iron storage in yeast requires the activity of the vacuolar iron transporter Ccc1. Yeast with an intact CCC1 are resistant to iron toxicity, but deletion of CCC1 renders yeast susceptible to iron toxicity. We used genetic and biochemical analysis to identify suppressors of high iron toxicity in Δccc1 cells to probe the mechanism of high iron toxicity. All genes identified as suppressors of high iron toxicity in aerobically grown Δccc1 cells encode organelle iron transporters including mitochondrial iron transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 35 publications
5
52
0
3
Order By: Relevance
“…Paradoxically, the same redox property makes this metal potentially toxic by causing oxidative stress (Halliwell & Gutteridge, 1984; Lin et al , 2011). Thus, iron homeostasis requires precise regulation of iron uptake and storage to satisfy the cellular needs but to avoid toxic iron excess.…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, the same redox property makes this metal potentially toxic by causing oxidative stress (Halliwell & Gutteridge, 1984; Lin et al , 2011). Thus, iron homeostasis requires precise regulation of iron uptake and storage to satisfy the cellular needs but to avoid toxic iron excess.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of this balance results in iron toxicity and cell death. Studies have shown that removing cytosolic iron either by sequestration in the vacuole or in the mitochondria can act as a protective mechanism against iron toxicity (Chen and Kaplan 2000; Li et al 2001; Lin et al 2011). Ccc1 plays a key role in this balance by importing iron into the vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this complexity, we decided to perform a first approach to analyze iron homeostasis in these strains at the molecular level. For this purpose, we cultivated yeast cells in liquid SC medium to reach the exponential growth phase and used quantitative reverse transcription-PCR (qPCR) to determine the mRNA levels of four genes that are crucial for iron uptake, distribution, and utilization: CTH2, which optimizes iron utilization within cells by regulating multiple iron-dependent metabolic pathways (12); FET3, a copper-dependent ferroxidase essential for high-affinity iron uptake (11); FET4, a low-affinity iron transporter located at the plasma membrane (7,8); and CCC1, responsible for iron transport and storage in the vacuole (15,16). It is worth highlighting that transcriptional activator Aft1 upregulates the expression of genes CTH2, FET3, and FET4 when yeast cells sense low iron (12,28), whereas Yap5 transcription factor increases CCC1 mRNA levels upon iron excess (14).…”
Section: Selection Ofmentioning
confidence: 99%
“…When environmental iron levels rise, the yeast Yap5 transcription factor activates specific genes that protect cells from the potential danger of high iron (14). The most relevant transcriptional activation by Yap5 is exerted on CCC1, which encodes a protein that protects cells from excess iron by transporting the metal from the cytoplasm to the vacuole, where it is stored (15,16). Recent studies have demonstrated that S. cerevi-siae does not directly sense extracellular or cytosolic iron concentrations.…”
mentioning
confidence: 99%